An electrochemical sensor based on silicon carbide / graphene material and its preparation method and application

By using silicon electrodes modified with silicon carbide/graphene materials in electrochemical sensors, the problems of low detection sensitivity and poor anti-interference ability in the prior art are solved, and high sensitivity, wide linear range and low detection limit are achieved. Dopamine detection has good selectivity and reproducibility.

CN115825180BActive Publication Date: 2024-12-17WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211085420.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-06
Publication Date
2024-12-17
Estimated Expiration
2042-09-06

AI Technical Summary

Technical Problem

Existing electrochemical sensors have problems with low sensitivity, narrow linear detection range and poor anti-interference ability when detecting dopamine. Especially in the presence of ascorbic acid and uric acid, it is difficult to accurately determine the dopamine concentration.

Method used

Silicon carbide/graphene material modified silicon electrodes are used to prepare silicon carbide/graphene composite films through laser chemical vapor deposition technology to form a three-dimensional porous network structure, improve conductivity and enhance catalytic activity, and realize selective detection of dopamine.

Benefits of technology

Dopamine detection with high sensitivity, wide linear detection range and low detection limit is achieved. It has good selectivity, reproducibility and anti-interference ability, and can accurately detect dopamine in the presence of ascorbic acid and uric acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115825180B_ABST
    Figure CN115825180B_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical sensor based on silicon carbide / graphene material and a preparation method and application thereof. The electrochemical sensor adopts a three-electrode system, with a silicon electrode modified by silicon carbide / graphene material as a working electrode, a saturated calomel electrode as a reference electrode, and a platinum sheet electrode as a counter electrode; the surface of the silicon electrode modified by silicon carbide / graphene material is covered with a silicon carbide / graphene composite film, the silicon carbide / graphene composite film is obtained by densely arranging branched silicon carbide nano whiskers perpendicular to a substrate, multilayer graphene is distributed on silicon carbide grain boundaries and the surface of the film, and a coherent pore structure is provided between the silicon carbide nano whiskers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrodes and relates to an electrochemical sensor based on silicon carbide / graphene material and a preparation method and application thereof. Background Art

[0002] The neurotransmitter dopamine (DA) plays an important role in the human body, including the cardiovascular, hormonal, renal and central nervous systems. Dopamine is secreted by neuronal cells and acts as a chemical messenger on target cells. The dopamine content of the extracellular fluid of the central nervous system is 0.01-1μM. Abnormal dopamine concentration is closely related to neurological diseases such as Parkinson's disease, attention deficit hyperactivity disorder, schizophrenia and depression. Therefore, accurate determination of dopamine content is very important for evaluating the progression of the disease.

[0003] There are many methods for detecting dopamine, such as liquid chromatography, UV-visible spectrophotometry, fluorescence spectrophotometry, and electrochemical methods. Electrochemical analysis methods have attracted much attention due to their high sensitivity, rapidity, accuracy, and simplicity. However, poor current signals are usually obtained on bare electrodes. In addition, molecules that coexist in actual samples, such as ascorbic acid and uric acid, may interfere with the determination of dopamine because they have similar redox potentials and higher concentrations to dopamine.

[0004] In order to solve the above problems, the applicant has developed a silicon carbide / graphene material to modify the bare electrode. Silicon carbide is considered to be a promising third-generation semiconductor due to its excellent physical and chemical properties, such as wide band gap, high hardness and good chemical stability. Cubic silicon carbide is a crystalline form of silicon carbide and is the only crystalline form that can grow on a silicon substrate. Cubic silicon carbide shows good biocompatibility and can be combined with the silicon-based semiconductor industry due to its deposition temperature below the melting point of silicon. These characteristics enable cubic silicon carbide to be used in implantable, miniaturized biomedical devices. However, silicon carbide is essentially an insulator with poor electrical conductivity, which limits its use. The present invention combines graphene with silicon carbide to significantly improve the conductivity of the material, thereby improving the detection capability of the electrochemical sensor. At the same time, the electrochemical sensor obtained after the silicon carbide / graphene material modifies the electrode can selectively detect dopamine in the presence of ascorbic acid and uric acid. Summary of the invention

[0005] The object of the present invention is to provide an electrochemical sensor based on silicon carbide / graphene material, a preparation method and application thereof, wherein the electrochemical sensor utilizes electrocatalytic oxidation to realize quantitative analysis of dopamine, has a wide linear detection range and a low detection limit for dopamine, and has excellent selectivity, reproducibility and repeatability.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0007] Provided is an electrochemical sensor based on silicon carbide / graphene material, wherein the electrochemical sensor adopts a three-electrode system, with a silicon electrode modified with silicon carbide / graphene material as a working electrode, a saturated calomel electrode as a reference electrode, and a platinum sheet electrode as a counter electrode;

[0008] The surface of the silicon electrode modified with silicon carbide / graphene material is covered with a silicon carbide / graphene composite film, which is obtained by densely arranging branched silicon carbide nano whiskers perpendicular to a substrate, multilayer graphene is distributed on silicon carbide grain boundaries and the surface of the film, and there is a coherent pore structure between the silicon carbide nano whiskers.

[0009] According to the above scheme, the thickness of the silicon carbide / graphene composite film is 5-500 μm.

[0010] According to the above scheme, the diameter of the silicon carbide nano whisker is 10-200nm, and the whisker length is 50-2000nm.

[0011] The present invention also includes a method for preparing the electrochemical sensor based on the silicon carbide / graphene material, wherein the specific steps for preparing the silicon electrode modified with the silicon carbide / graphene material are as follows:

[0012] 1) Place the cleaned substrate into the deposition chamber of the laser chemical vapor deposition equipment, and adjust the position of the substrate so that it is within the laser coverage range;

[0013] 2) The deposition chamber is evacuated to below 20 Pa, and a dilution gas H2 and a carrier gas Ar containing a precursor are introduced, and the pressure is adjusted to the deposition pressure;

[0014] 3) Turn on the laser heating program to heat the substrate. When the displayed temperature is the deposition temperature, start timing. After the deposition is completed, turn off the laser, precursor gas, carrier gas, and dilution gas in sequence. When the substrate temperature displays 300°C, break the vacuum (as the temperature decreases, the oxygen entering the cavity will oxidize the graphene, resulting in a decrease in the graphene content of the thin film), take out the substrate, and obtain a silicon electrode modified with silicon carbide / graphene material.

[0015] According to the above scheme, the substrate in step 1) is selected from one of a single crystal silicon wafer, a polycrystalline silicon wafer, a graphite felt, and a graphite sheet, and the diameter of the substrate is 0.4-4 inches.

[0016] According to the above scheme, the precursor in step 2) is one or more of hexamethyldisilane, methyltrichlorosilane, silicon tetrachloride, trichlorosilane, methane, propane, ethylene, acetylene, and hydrogen.

[0017] According to the above scheme, the deposition pressure in step 2) is 50-5000Pa.

[0018] According to the above scheme, the deposition temperature in step 3) is 1000-1500°C.

[0019] The present invention also includes the application of the electrochemical sensor based on silicon carbide / graphene material in detecting dopamine.

[0020] The electrochemical sensor based on silicon carbide / graphene material of the present invention uses a silicon electrode modified by silicon carbide / graphene material as a working electrode. The silicon carbide / graphene material has a three-dimensional porous network structure, which can fully contact with the electrolyte, which is conducive to exposing more catalytic active sites in the electrochemical reaction process. At the same time, the silicon carbide / graphene material shows a lower charge transfer resistance and a higher electron transfer rate. The silicon electrode modified by silicon carbide / graphene material has a strong anti-interference ability against ascorbic acid and uric acid, and can achieve selective detection of dopamine.

[0021] The beneficial effects of the present invention are:

[0022] 1. The electrochemical sensor based on silicon carbide / graphene material provided by the present invention is used for dopamine detection, has high sensitivity, wide linear detection range, low detection limit, good selectivity and repeatability;

[0023] 2. The present invention directly deposits a silicon carbide / graphene composite film on a silicon substrate, which is compatible with traditional silicon electronic devices to construct an integrated bioelectronic system. The preparation process is time-saving and has good reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD (a) and Raman spectrum (b) of the silicon carbide / graphene composite film prepared in Example 1 of the present invention;

[0025] Figure 2 This is a field emission scanning microscope image of the silicon carbide / graphene composite film prepared in Example 1;

[0026] Figure 3 This is a transmission electron microscope image of the silicon carbide / graphene composite film prepared in Example 1;

[0027] Figure 4 Cyclic voltammograms at different scan rates (a), peak current versus scan rate square root diagram (b), and electrochemical impedance spectrum (c) of the electrochemical sensor based on silicon carbide / graphene material prepared in Example 2 in a 0.1 M KCl solution containing K3Fe(CN)6 and K4Fe(CN)6 (the molar ratio of K3Fe(CN)6 to K4Fe(CN)6 is 1:1, and the total concentration of the two is 5.0 mM);

[0028] Figure 5Cyclic voltammetry curves of the electrochemical sensor based on silicon carbide / graphene material prepared in Example 2 in phosphate buffer solutions without and with 0.5 mM dopamine;

[0029] Figure 6 The differential pulse voltammetry curves (a) and the relationship between the oxidation peak current and the concentration (b) of the electrochemical sensor based on silicon carbide / graphene material prepared in Example 2 for detecting dopamine at different concentrations;

[0030] Figure 7 The differential pulse voltammetry curves (a) and the chronoamperometric curves (b) of the electrochemical sensor based on silicon carbide / graphene material prepared in Example 2 measured at different uric acid concentrations in the presence of different interfering substances;

[0031] Figure 8 Reproducibility (a) and repeatability (b) test results of electrochemical sensors. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0033] All electrochemical tests in the examples of the present invention, including cyclic voltammetry, electrochemical impedance spectroscopy, differential pulse voltammetry and chronoamperometry, were performed on a CHI660E electrochemical workstation at room temperature.

[0034] Example 1

[0035] The specific preparation steps of silicon carbide / graphene material modified silicon electrode are as follows:

[0036] 1) Place a cleaned single crystal silicon substrate (0.6 inch in diameter) into the deposition chamber of a laser chemical vapor deposition device, and adjust the position of the substrate so that it is within the laser coverage range;

[0037] 2) The deposition chamber was evacuated to below 20Pa, and a dilution gas H2 and a carrier gas Ar containing a precursor HMDS were introduced, with an H2 flow rate of 500sccm, an H2 purity of 99.999vol%, an Ar flow rate of 25sccm, an Ar purity of 99.999vol%, an HMDS flow rate of 1sccm, and the deposition pressure was adjusted to 1400Pa;

[0038] 3) Turn on the laser heating program to heat the substrate. When the displayed temperature is 1200°C, the timing starts. The deposition time is 25 minutes. After the deposition is completed, turn off the laser, precursor gas, carrier gas, and dilution gas in sequence. When the substrate temperature displays 300°C, break the vacuum, take out the substrate, and deposit a silicon carbide / graphene composite film on the surface of the single crystal silicon substrate, which is a silicon electrode modified with silicon carbide / graphene materials.

[0039] The XRD and Raman spectra of the silicon carbide / graphene composite film obtained in this embodiment are as follows: Figure 1 As shown in Figure 2, the diffraction peaks at 35.6°, 59.9°, 71.7°, and 75.3° correspond to the (111), (220), (311), and (222) crystal planes of cubic silicon carbide, respectively. Figure 1 (a)), indicating that the film is composed of cubic silicon carbide. Figure 1 (b) The characteristic peaks of graphene, D peak, G peak and 2D peak, can also be observed. The existence of D peak indicates the existence of defects in graphene. The ratio of 2D peak to G peak intensity is 0.11, indicating that there are many graphene layers. In the Raman spectrum, not only the characteristic peaks of graphene can be seen, but also the characteristic peaks of silicon carbide, TO peak and LO peak, indicating that the film is a silicon carbide / graphene composite material.

[0040] Figure 2 The field emission scanning microscope images of the silicon carbide / graphene composite film prepared in this embodiment, wherein (a) is the surface morphology of the film, (b) is the cross-sectional morphology of the film, and (c) is an enlarged view of the box portion in (b). It can be seen that the film prepared in this embodiment has a thickness of 63 μm, and the film is a dendritic silicon carbide nanowhisker grown vertically on the substrate, with a whisker diameter of 60-80 nm and a whisker length of 160-200 nm. There are interconnected pore structures between the silicon carbide nanowhiskers, which is conducive to full contact between the film and the electrolyte.

[0041] Figure 3 (a) is a transmission electron microscope image of the silicon carbide / graphene composite film prepared in this embodiment, (b) and (c) are enlarged images of the corresponding areas in (a), and it can be seen that multilayer graphene is distributed on the surface of the film and the silicon carbide grain boundaries.

[0042] Example 2

[0043] Electrochemical sensors based on silicon carbide / graphene materials and their applications in detecting dopamine:

[0044] The electrochemical sensor adopts a three-electrode system, with the silicon carbide / graphene-modified silicon electrode prepared in Example 1 as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum sheet electrode as the counter electrode. The area of ​​the electrodes immersed in the solution is fixed at 1 cm 2 In a 0.1M KCl solution containing K3Fe(CN)6 and K4Fe(CN)6 (the molar ratio of K3Fe(CN)6 to K4Fe(CN)6 was 1:1, and the total concentration of the two was 5.0mM), the current response curves of the silicon carbide / graphene electrode at different scan rates (scan rate of 20-160mV / s) were tested by cyclic voltammetry ( Figure 4 (a)), and then the relationship between peak current and the square root of scan rate was obtained ( Figure 4(b)). As the scan rate increases, the peak current value of dopamine oxidation on the electrode (I pa ) also increases and is proportional to the square root of the scanning speed (v 1 / 2 ) is linearly related, and the linear equation is I pa =0.00508v 1 / 2 +0.00029(R 2 =0.99483). Combining the Randles-Sevcik equation, we know that the electrochemical active area of ​​the film is 1.37 cm 2 , higher than the geometric area of ​​the film (1cm 2 ). Test the charge transfer resistance of the film, the test frequency ranges from 10mHz to 10 KHz, the test voltage is the open circuit voltage, and the electrochemical impedance spectrum is shown in Figure 4 (c), the charge transfer resistance of the film is found to be 16.1Ω.

[0045] The cyclic voltammetry curves of the electrochemical sensor in a phosphate buffer solution with a pH value of 7.4 and without dopamine, and in a phosphate buffer solution with a pH value of 7.4 and containing 0.5 mM dopamine, are detected. Figure 5 As shown, the test potential window is -0.2V~0.6V, the CV curve is a rectangular shape, the curve is symmetrically distributed about 0 current, and there is no redox peak. When 0.5mM dopamine is added to the solution system, a pair of obvious redox peaks appear, indicating that dopamine undergoes a redox reaction on the electrode, indicating that the silicon electrode modified with silicon carbide / graphene material has a detection effect on dopamine.

[0046] Differential pulse voltammetry was used to measure the current response of the electrochemical sensor to different concentrations of dopamine. Dopamine solutions of different concentrations (0.5 μM, 1.5 μM, 3.5 μM, 8.5 μM, 18.5 μM, 38.4 μM, and 78.0 μM) were added to the PBS solution. The test potential range was -0.1 to 0.4 V, the amplitude was 50 mV, and the pulse width was 50 ms. Figure 6 (a) shows the differential pulse voltammetry curve of the detection of dopamine solutions with different concentrations. It can be seen that as the concentration of the substance to be tested, dopamine, increases, the response current gradually increases. (b) is the relationship curve between the oxidation peak current and the concentration, which proves that the oxidation peak current has a good linear relationship with the concentration. pa (μA)=25.10025+0.86393C(μM)(R 2 =0.99102), the linear detection range was 0.5-78 μM, and the detection limit was as low as 0.11 μM.

[0047] Differential pulse voltammetry was used to detect the anti-interference ability of the electrochemical sensor against ascorbic acid and uric acid. Different concentrations of uric acid were added to PBS solutions containing 50 μM dopamine and 500 μM ascorbic acid. The concentrations of uric acid were 0 μM, 50 μM, 150 μM, 300 μM, and 500 μM, respectively. The detection potential range was -0.1 to 0.4 V, the amplitude was 50 mV, and the pulse width was 50 ms. Figure 7 (a) shows the differential pulse voltammetry curves measured at different uric acid concentrations. When 500 μM ascorbic acid and 50 μM dopamine were added to a phosphate buffer solution with a pH of 7.4, only the oxidation peak of dopamine was observed, and no current signal of ascorbic acid was observed. Subsequently, different concentrations of uric acid were added to the solution, and it was observed that the oxidation peaks of dopamine and uric acid were well separated, indicating that the electrochemical sensor has good anti-interference ability to ascorbic acid and uric acid. The electrochemical sensor was tested for other interfering substances such as K using chronoamperometry. + , Cl - 、SO4 2- and Na + Anti-interference ability, such as Figure 7 (b) shows the chronoamperometric curves of the electrochemical sensor in the presence of different interfering substances. After adding 50 μM dopamine to the phosphate buffer solution, the current increased significantly. + , Cl - 、SO4 2- 、Na + The above test results show that the above electrochemical sensor is not sensitive to ascorbic acid, uric acid, and K coexisting in the dopamine detection system. + , Cl - 、SO4 2- 、Na + All have anti-interference capabilities.

[0048] Six silicon electrodes modified with silicon carbide / graphene materials were prepared by the method described in Example 1. Six electrochemical sensors were made according to the above method. The dopamine oxidation peak current of the six electrochemical sensors was detected by differential pulse voltammetry in a phosphate buffer solution with a pH value of 7.4 and containing 200 μM dopamine. The comparison diagram is shown in FIG. Figure 8 As shown in (a), the relative standard deviation of the dopamine oxidation peak current values ​​measured by the six electrochemical sensors was 1.99%, showing acceptable reproducibility.

[0049] One of the silicon electrodes modified with silicon carbide / graphene materials was selected and an electrochemical sensor was made according to the above method. The dopamine oxidation peak current of the electrochemical sensor was detected in a phosphate buffer solution with a pH value of 7.4 and containing 100 μM dopamine by differential pulse voltammetry. The detection was repeated 8 times. The comparison of the test values ​​is shown in the figure below. Figure 8 As shown in (b), the relative standard deviation of the measured dopamine oxidation peak current value is 3%, indicating that the electrode has good repeatability.

[0050] In summary, the sensor provided by the embodiment of the present invention has the characteristics of a wide linear range, a low detection limit, good selectivity, reproducibility and repeatability for the detection of dopamine.

[0051] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. For those skilled in the art, the present invention may have various modifications and changes. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be within the scope of protection of the present invention.

Claims

1. An electrochemical sensor based on silicon carbide / graphene material, characterized in that: The electrochemical sensor adopts a three-electrode system, with a silicon electrode modified with silicon carbide / graphene material as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum electrode as the counter electrode; The surface of the silicon electrode modified with the silicon carbide / graphene material is covered with a silicon carbide / graphene composite film, wherein the silicon carbide / graphene composite film is obtained by densely arranging branched silicon carbide nano whiskers perpendicular to a substrate, multilayer graphene is distributed on the silicon carbide grain boundaries and the film surface, and there is a coherent pore structure between the silicon carbide nano whiskers; The thickness of the silicon carbide / graphene composite film is 5-500 μm, the diameter of the silicon carbide nano whisker is 10-200 nm, and the whisker length is 50-2000 nm.

2. A method for preparing an electrochemical sensor based on silicon carbide / graphene material according to claim 1, characterized in that: The specific preparation steps of the silicon electrode modified with silicon carbide / graphene material are as follows: 1) Place the cleaned substrate into the deposition chamber of the laser chemical vapor deposition equipment and adjust the position of the substrate so that it is within the laser coverage range; 2) The deposition chamber is evacuated to below 20 Pa, and the dilution gas H2 and the carrier gas Ar containing the precursor are introduced, and the deposition pressure is adjusted to 50-5000 Pa; 3) Turn on the laser heating program to heat the substrate. When the displayed temperature is the deposition temperature, start timing. The deposition temperature is 1000-1500 °C. After the deposition is completed, turn off the laser, precursor gas, carrier gas, and dilution gas in sequence. When the substrate temperature displays 300 °C, break the vacuum and take out the substrate to obtain a silicon electrode modified with silicon carbide / graphene material.

3. The method for preparing an electrochemical sensor based on silicon carbide / graphene material according to claim 2, characterized in that: Step 1) The substrate is selected from one of a single crystal silicon wafer, a polycrystalline silicon wafer, a graphite felt, and a graphite sheet, and the diameter of the substrate is 0.4-4 inches.

4. The method for preparing an electrochemical sensor based on silicon carbide / graphene material according to claim 2, characterized in that: Step 2) The precursor is one or more of hexamethyldisilane, methyltrichlorosilane, silicon tetrachloride, trichlorosilane, methane, propane, ethylene, acetylene, and hydrogen.

5. Use of the electrochemical sensor based on silicon carbide / graphene material according to claim 1 in detecting dopamine.